Meningkatkan Kemampuan Memakai Kaos Kaki Melalui Video Tutorial Berbasis Modeling pada Anak Disabilitas Intelektual (Single Subject Research Kelas IX di SLB C Muzdalifah Medan) - Ramadhani; Tsaputra, Antoni; Iswari, Mega; Taufan, Johandri (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to determine the effect of modeling-based tutorial videos on the ability of children with intellectual disabilities to put on socks. The study uses Single Subject Research (SSR) with an A–B–A design, including Baseline 1 (A1), Intervention (B1), and Baseline 2 (A2). The research subject is one student. Data were collected through observation of sock-wearing activities and recorded in the percentage of ability for each session. The research results indicate that the students' abilities in Baseline 1 were still low, at 38.10%–42.85%. During the intervention, it gradually increased to 52.38%–76.19%. In Baseline 2, the abilities remained higher compared to Baseline 1, although slightly decreased to 52.38%–71.43%. This shows that modeling-based tutorial videos are effective in improving the abilities of children with intellectual disabilities in the activity of putting on socks.